GOBIS: Transformasi Digital dalam Tata Kelola Smart Mobility yang Berkelanjutan di Kota Surabaya - Yuyun Eka Kartika Sari; Deby Febriyan Eprilianto; Weni Rosdiana; Yuni Lestari; Muhammad Khairul Anwar (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
The growing challenge of sustainable urban development has positioned digital transformation as a critical strategy to enhance the effectiveness and accountability of public service governance. This study explores the strategic role of the GOBIS application in advancing digital transformation toward sustainable smart mobility governance in Surabaya. Using a qualitative descriptive approach, data were collected through literature studies, direct observations, Focus Group Discussions (FGDs), and in-depth interviews with representatives of the Surabaya City Government and public transportation users. The research findings indicate that GOBIS plays a central role as a socio-technical instrument in supporting sustainability across three key dimensions. First, it enhances operational efficiency, transparency, and data integration, which strengthens both economic and institutional sustainability. Second, by providing real-time travel information, route tracking, and an intuitive user interface, GOBIS improves the reliability and attractiveness of public transportation, encouraging a shift from private vehicles to mass transit and thereby supporting environmental sustainability. Third, it expands accessibility and inclusiveness of transport services, contributing to social sustainability by enabling more equitable urban mobility. However, the implementation of GOBIS also faces several challenges, including unequal digital literacy among users, technical stability issues, and the limited integration of participatory features for user feedback. These factors may constrain the full realization of its potential. Therefore, optimizing GOBIS as an inclusive, adaptive, and participatory digital platform is essential to accelerate the development of an integrated, inclusive, and sustainable urban transportation ecosystem in Surabaya